Pengaruh Pengetahuan Kewirausahaan dan Self Efficacy Terhadap Minat Berwirausaha Mahasiswa (Studi Kasus Pada Mahasiswa Program Studi Kewirausahaan Universitas Malikussaleh) - Juliana, Juliana .; Munandar, Munandar .; Agustinawati, Agustinawati .; Samsidar, Samsidar . (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
This research aims to determine the influence of Entrepreneurship knowledge and Self Efficacy on Entrepreneurship Interest in Entrepreneurship Study Program Students. The respondents in this research were students from the Malikussaleh University Entrepreneurship Study Program. This research sample was taken using random sampling technique. The data collected was 116 respondents using Google Form. The collected data was analyzed using multiple linear regression analysis with the help of Excel and the SPSS 20 application. The research results showed that knowledge of Entrepreneurship had a positive and significant effect on interest in entrepreneurship in the Malikussaleh University Entrepreneurship Study Program Self Efficacy has no significant effect on the entrepreneurial interest of students in the Malikussaleh University entrepreneurship study program. Keywords: Entrepreneurship Knowledge, Self Efficacy, Interest in Entrepreneurship.